2017
DOI: 10.3746/pnf.2017.22.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Differences of Waxy Barley Flour Dispersions Mixed with Various Gums

Abstract: Rheological properties of waxy barley flour (WBF) dispersions mixed with various gums (carboxyl methyl celluleose, guar gum, gum arabic, konjac gum, locust bean gum, tara gum, and xanthan gum) at different gum concentrations were examined in steady and dynamic shear. WBF-gum mixture samples showed a clear trend of shear-thinning behavior and had a non-Newtonian nature with yield stress. Rheological tests indicated that the flow and dynamic rheological parameter (apparent viscosity, consistency index, yield str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The G″ values of RS+TG samples were remarkably increased compared to the values of G′ of RS pastes, resulting in the increase of tan δ values of RS+TG pastes. This result was similar to Lee et al ( 19 ) and Kim and Yoo ( 20 ). Lee et al ( 19 ) reported that both G″ and tan δ values of rice starch were increased in the presence of TG.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The G″ values of RS+TG samples were remarkably increased compared to the values of G′ of RS pastes, resulting in the increase of tan δ values of RS+TG pastes. This result was similar to Lee et al ( 19 ) and Kim and Yoo ( 20 ). Lee et al ( 19 ) reported that both G″ and tan δ values of rice starch were increased in the presence of TG.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, the K and η a,500 of all RS+TG pastes were significantly higher than those of RS with increasing amounts of TG. Similar findings were observed by Kim and Yoo ( 20 ). They observed that the addition of TG to waxy barley flour dispersions had a significant increase in the K and η a,100 values of waxy barley flour dispersions.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Beakers were heated in a water bath (Memmert, Schwabach, Germany) at 60°C for 5 min to pre-gelatinise the GRF dispersions with manual stirring every 15 s, to prevent sedimentation of flour that causes a separation and leads to formation of two layers. Then, they were transferred to a shaking thermostatic water bath (WB22-16X2501, Memmert, Schwabach, Germany) at 95°C for 30 min with a mild agitation (Chun and Yoo 2004;Kim and Yoo 2017) provided by water bath shaker to minimize settling of flour particle. Gelatinisation that occurs during cooking allows leaching of amylopectin from starch granules for enzymatic hydrolysis due to high susceptibility of gelatinised starch to enzymatic action (Holm et al 1988;Thomas and Atwell 1997).…”
Section: Preparation Of Flour Dispersionmentioning
confidence: 99%